2002
DOI: 10.1128/jcm.40.6.2308-2310.2002
|View full text |Cite
|
Sign up to set email alerts
|

Enterococcus gallinarum Endocarditis Occurring on Native Heart Valves

Abstract: We report the first case of Enterococcus gallinarum endocarditis developing on normal native heart valves. Using phenotypic and molecular methods, a precise identification of this naturally vancomycin-resistant species allowed an optimal antibiotic therapy and the patient's recovery. CASE REPORTA 62-year-old Vietnamese man was admitted to our hospital in January 2001 because of presumptive endocarditis. He had been living in France since 1952 and worked as a veterinarian. He had a background history of cholecy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 31 publications
(24 reference statements)
0
26
1
1
Order By: Relevance
“…or chronically ill patients, and sometimes are nosocomially acquired (Reid et al 2001, Dargere et al 2002. In this study the prevalence of vanC phenotype enterococci was significantly higher (23.7% of E. gallinarum and 5.2% of E. casseliflavus) than in several studies that reported intestinal colonization by enterococci vanC.…”
Section: Discussioncontrasting
confidence: 57%
“…or chronically ill patients, and sometimes are nosocomially acquired (Reid et al 2001, Dargere et al 2002. In this study the prevalence of vanC phenotype enterococci was significantly higher (23.7% of E. gallinarum and 5.2% of E. casseliflavus) than in several studies that reported intestinal colonization by enterococci vanC.…”
Section: Discussioncontrasting
confidence: 57%
“…E. faecalis and E. faecium are the two most commonly encountered enterococcal species, together accounting for 90% of isolates 6,8 . Other species, including E. gallinarum are uncommonly encountered in human clinical specimens and are primarily found in the gastrointestinal tracts in poultry 3,8 . Infection by E. gallinarum rarely occurs and has been implicated in a few invasive infections in humans, especially in immunocompromised or chronically ill patients 2,3,5 .…”
Section: Introductionmentioning
confidence: 99%
“…Other species, including E. gallinarum are uncommonly encountered in human clinical specimens and are primarily found in the gastrointestinal tracts in poultry 3,8 . Infection by E. gallinarum rarely occurs and has been implicated in a few invasive infections in humans, especially in immunocompromised or chronically ill patients 2,3,5 . There are only four cases of CNS involvement reported in literature due to this unusual germ, all reporting on patients with some degree of immunosuppression who had been previously submitted to a neurological procedure 4,8,9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, due to the higher incidence of infections by enterococci in young, older and immunocompromised patients, and to their extended resistance to antibiotics, they are being considered as emerging pathogens [6,7]. The majority of infections are caused by either E. faecalis or E. faecium strains, [8,9] However, strains of E. gallinarum [10], E. hirae [11], and E. mundtii [12] have been also associated with endophtalmitis and native valve endocarditis in humans.…”
Section: Introductionmentioning
confidence: 99%